2008
DOI: 10.1007/s12253-008-9091-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mobilisation of Hematopoietic Stem Cells After Hepatic Resection for Malignant Liver Disease

Abstract: Recent studies have demonstrated that hematopoietic stem cells (HSCs) can mobilize following liver resection, thus contributing to the repair of hepatic damage. Aim of this study has been to determine whether the nature of the hepatic lesion (benign vs. malignant disease) can give rise to a different degree of mobilisation of HSCs. Two groups of patients were selected: the first included seven patients undergoing hepatic resection (five major and two minor) for a benign liver disease (focal nodular hyperplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…22 Menegazzo et al have shown that the type of the hepatic lesion influences the regenerative response after hepatic resection, with a reduced mobilization of HSC in the malignant liver diseases. 21 In the present study, the analysis of a comparatively higher number of patients has shown no association between the levels of CD34 + cells and the clinical characteristic of the patients. However, it is interesting to note that the patients with hepatocellular carcinoma and metastasis showed lower percentages of BMSC mobilization (14% and 40%, respectively) compared to other type of pathologies.…”
Section: Discussioncontrasting
confidence: 61%
“…22 Menegazzo et al have shown that the type of the hepatic lesion influences the regenerative response after hepatic resection, with a reduced mobilization of HSC in the malignant liver diseases. 21 In the present study, the analysis of a comparatively higher number of patients has shown no association between the levels of CD34 + cells and the clinical characteristic of the patients. However, it is interesting to note that the patients with hepatocellular carcinoma and metastasis showed lower percentages of BMSC mobilization (14% and 40%, respectively) compared to other type of pathologies.…”
Section: Discussioncontrasting
confidence: 61%
“…This hypothesis was adopted by an important study reporting the reduced mobilization of BMHSC in malignancy after hepatic resection. This effect was found to be caused by the downregulation of some factors including stromal cell‐derived factor (SDF), matrix metalloproteinases, hepatocyte growth factor and interleukin‐8 …”
Section: Discussionmentioning
confidence: 99%
“…This effect was found to be caused by the downregulation of some factors including stromal cell-derived factor (SDF), matrix metalloproteinases, hepatocyte growth factor and interleukin-8. 27 Lack of BMHSC mobilization to the circulation was then confirmed by the failure of such cells to engraft in the hepatic tissue. No difference in the frequency of CD133 + stem cells was found in injured liver tissue with variable degrees of severity, denoting that neither residing nor BMHSC were activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After resection of FNH and hemangioma tumors, the serum levels of HGF, IL-6, and TGF-a increased at similar rates during the first 24 h, followed by significant declines back to pre-operative levels. cell (HSC) mobilization after liver resection of a malignant disease [31]. Additionally, HSC's were shown to play a role in the production of humoral factors which indirectly support hepatic recovery and may induce an alternate regenerative response depending on the nature of the lesion [32].…”
Section: Introductionmentioning
confidence: 99%